Srovnávací studie vybraných hledisek vývoje národní identity u dětí litevské a polské většiny a menšiny - Sawicki, Wojciech (Lidé města, 2002)
The study introduces a research project designed to compare the national identity of the children of the Lithuanian and Polish majority and minority in Poland. The project sought to understand the process of the development of national identity, national attitudes and prejudices as well as highlighting of the background upon which national identity of the "forthcoming generation" is being shaped. The sample of the respondents under consideration included seven age groups from four-year-old children to 16-year teenagers. As a result, the research monitors identity attitudes of children from the very beginning of the understanding of this phenomenon to the age of puberty. Of the aspects of national identity only the following were taken into account: (1) the importance of national identity in one's own mind; (2) the cognitive approach to foreigners and members of one's own nation; and (3) the knowledge of children of the process when they become members of a nation and their understanding of the process. This was motivated by the importance of national identity in one's own mind; the cognitive approach to foreigners and members of one's own nation; and the understanding of the process when children become members of a nation. The research mainly wanted to find answers to the following questions: 1. Do children under norma! circumstances denote themselves by means of categories of national identity and is this dimension of their identification important for them? 2. What are the criteria allowing a certain child to identity people with this or that nation? (The answer to this question will also help us ascertain what are the attitudes of children to the members of other nations and what is their definition of a nation.) 3. How do the children understand the process when they become members of a nation and what do they know about it? The study submits a research project of certain aspects in the development of national identity. The research is still continuing and only a part of the data has been collected. We will obtain through the research three types of information: 1. The data about the children themselves as revealed by them (the importance of the dimension of national identity); 2. The attitude of the children to the members of their own as well as other nations; 3. The children's knowledge of the process of integration into their own nation.